2007
DOI: 10.1111/j.1465-7287.2007.00042.x
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Interpretation of Suicide Cycles in Japan

Abstract: "Suicide rates in Japan have increased dramatically in recent years, making Japan's male rate the highest among developed economies. This study revises the standard economic model of suicide to accommodate Japan's experience, focusing on the change in human capital for the unemployed. We then use the new model and detrended data to empirically investigate the relationship between the suicide cycle and the unemployment cycle. Unlike previous aggregate time series studies, we find that the relationship between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
85
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 28 publications
7
85
0
6
Order By: Relevance
“…The empirical literature on suicide reports evidence that divorce is positively associated with suicide rates [20], [23], [24], [31], [15], [22]. Also, some papers show that the male suicide rate is more sensitive to divorce than the female suicide rate [29], [20], [32], [22]. Again, endogeneity concerns are relevant here, as divorce might be related to mental health problems.…”
Section: Literature Reviewmentioning
confidence: 94%
See 2 more Smart Citations
“…The empirical literature on suicide reports evidence that divorce is positively associated with suicide rates [20], [23], [24], [31], [15], [22]. Also, some papers show that the male suicide rate is more sensitive to divorce than the female suicide rate [29], [20], [32], [22]. Again, endogeneity concerns are relevant here, as divorce might be related to mental health problems.…”
Section: Literature Reviewmentioning
confidence: 94%
“…The unemployment rate is often used as a proxy variable for economic hardships and lifetime earnings, because measuring an person's agent's lifetime income is not easy in practice [29]. But unemployment might be also associated with factors such as depressive episodes, anxiety, and loss of selfconfidence that might lead directly to suicide.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-one studies examined suicides or attempted suicides and found a marked increase in these outcomes during economic downturns. 12,17,18,37,39,63,71,78,79,89,91,97,103,116,117,[120][121][122][123][124]126 The increases in suicides were concentrated in working age men, and the results were found across multiple populations including the United Kingdom, 63,78 the US, 12 Spain, 121 Italy 122 and Japan 116,120,123 as well as across time periods. 18,39 The relationship between unemployment and suicides does seem to be context specific because such relationships have not been found in Sweden, 79 Finland, 89,91 and Australia.…”
Section: Substance Abuse and Mental Healthmentioning
confidence: 99%
“…2 In Japan in the 21st century, suicide became a more serious issue than in prior centuries; hence, it is crucial to implement measures to prevent suicide. 3 Economic researchers have provided evidence that the increase in the suicide rate was caused partly by the economic conditions (e.g., Koo and Cox 2008;Chen et al 2009;Inagaki 2010;Kuroki 2010;Sugano and Matsuki 2014, Suzuki et al 2013;2014). 4 However, consistent with Durkheim's view, social factors are also significantly related to the suicide rate in Japan (e.g., Yamamura 2010, Andrés et al 2011; Sugano and Matsuki 2014).…”
Section: Introductionmentioning
confidence: 97%